Health Quality in Brebes District, Central Java: Stunting Prevalence in the Light of Galtung's Violence Triangle - Ambika Putri Swakartika Sari (CV. Abhinaya Indo Group, 2025)
The dynamics of development in one of the regencies in Central Java Province, namely Brebes Regency, is analogous to a Greek mythological “pandora's box” as a metaphor for the “many problems and difficulties that exist within it”. The “Pandora's Box” referred to in the context of development in Brebes District is the low quality of health services characterized by the high prevalence of stunting (stunted children). The research question formulated is why the prevalence of stunting in Brebes Regency, Central Java continues to occur and what factors are at the root of the problem from the perspective of Galtung's Violence Triangle concept. The findings of this research are that the high prevalence of stunting is due to the intersection/interconnection between Galtung's three forms of violence. Direct violence occurs verbally, which hits the psyches of families with stunted children in the form of social stigma and physically in the form of domestic violence, both of which are allowed to become a culture of silence in society. Structural violence occurs in unfair social structures and systems that further exacerbate poverty and inequality, inadequate access to health facilities and services, low community literacy, especially pre-marital provision knowledge, and unequal access to clean water, environmental sanitation and the absence of local food diversification. At the same time, cultural violence also works to strengthen and legitimize the direct and structural violence that occurs, such as the existence of the key.